THE INFLUENCE OF PERCEIVED TEACHERS’ COMPETENCES ON STUDENTS’ MOTIVATIONS IN LEARNING ENGLISH AT PESANTREN PKP AL-HIDAYAH JAMBI CITY - Harun Muzammil, Jonaidi; Sulistiyo, Urip; Haryanto, Eddy (JELT (Jambi-English Language Teaching), 2026)
This study investigates the influence of perceived teachers’ competences on students’ motivation in learning English at Pesantren PKP Al-Hidayah, Jambi City. Grounded in Indonesian teacher competency standards pedagogical, professional, personality, and social competences this quantitative research employed a regression design to examine the influence between teacher competence and students’ intrinsic and extrinsic motivation. Data were collected from 224 senior high school students using validated Likert-scale questionnaires adapted from established instruments. Multiple linear regression analyses were conducted using SPSS 22.0. The findings reveal that students perceived teachers’ competences to be generally high across all dimensions, with personality competence demonstrating the highest mean score. Students’ motivation to learn English was also found to be high, particularly intrinsic motivation. These results suggest that competent teachers especially those exhibiting strong personal qualities and effective pedagogical practices play a crucial role in fostering students’ internal engagement and sustained motivation in English learning. The study contributes empirical evidence from an Islamic boarding school context and underscores the importance of continuous teacher professional development to enhance student motivation in EFL settings.